Physical and electrical properties of Nb doped Bi0.5Na0.5[Zr0.59Ti0.41]O3 - Ampika Rachakom (2018)
This research studied the effect of Nb doping on Bi0.5Na0.5[Ti0.41Zr0.59]O3(when Nb concentration = 0.00, 0.01, 0.03, 0.05, 0.07 and 0.09 mol fraction). Nb doped BNTZ ceramics were fabricated using a conventional mixed-oxide method. All samples were calcined at a temperature of 700°C for 2 h and sintered at a temperature of 900°C for 2 h. X-ray diffraction patterns suggested that the compounds possessed rhombohedral perovskite structure. SEM micrographs indicated that average grain size decreased as the amount of Nb additives increased. The electrical resistivity showed a decreasing trend with increasing Nb concentration due to excess charge present in the sample. The dielectric constant and dielectric loss of samples showed no particular trend when Nb was added but the optimum was observed when 0.05-0.07 Nb mol fraction was present in BNTZ ceramics. In this study, both microstructure and donor-type effects played an important role in determining electrical resistivity and dielectric properties of these ceramics. © 2011 Elsevier Ltd and Techna Group S.r.l.